Sleep Disorders Medicine Basic Science, Technical Considerations and Clinical Aspects - Chokroverty, Sudhansu; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2017)
Since publication of the first edition in 1994, the second edition in 1999, and the third edition in 2009, many new advances in sleep medicine have been made and warrant a fourth edition. This comprehensive text features 19 additional chapters and covers basic science, technical and laboratory aspects and clinical and therapeutic advances in sleep medicine for beginners and seasoned practitioners. With the discovery of new entities, many new techniques and therapies, and evolving basic science understanding of sleep, Sleep Disorders Medicine, Fourth Edition brings old and new knowledge about sleep medicine together succinctly in one place for a deeper understanding of the topic. Neurologists, internists, family physicians, pediatricians, psychiatrists, psychologists, otolaryngologists, dentists, neurosurgeons, neuroscientists, intensivists, anesthesiologists as well as those interested in advancing their knowledge in sleep and its disorders, will find this edition to be an invaluable resource to this bourgeoning field.
Keywords: Medicine; General practice (Medicine).; Neurology; Otorhinolaryngology; Psychiatry; Medicine & Public Health; Neurology; Otorhinolaryngology; General Practice / Family Medicine; Psychiatry